Dyslipidemia and serum mineral profiles in patients with thyroid disorders - Abdel-Gayoum, Abdelgayoum A. (Saudi Medical Journal, 2014)
OBJECTIVES: To investigate changes in serum lipid profile, levels of serum minerals associated with thyroid disorders, and to compare these with the serum lipid and mineral profiles in hypothyroid patients receiving thyroxine therapy.METHODS: A cross-sectional study was conducted in King Khaled Hospital, Hail, Saudi Arabia. The patient database was searched for new patients with thyroid dysfunction between January 2011 and June 2012. They were classified into 5 groups: 1) subclinical-hypothyroid (SHY), 2) overt-hypothyroid (OHY), 3) subclinical-hyperthyroid (SHE), 4) overt-hyperthyroid (OHE), 5) patients under thyroxine therapy (EU), and normal controls.RESULTS: The OHY group showed impaired renal function; whereas, the kidney function of the SHE, OHE, and EU groups was normal. The OHY and OHE groups exhibited elevated serum glucose. The OHY group showed elevated serum cholesterol, triglyceride, and low-density lipoprotein cholesterol, and decreased high-density lipoprotein cholesterol. Serum lipids were reduced in the OHE group, and no different in the EU group compared with controls. The serum calcium and phosphate were reduced in the OHY group, whereas, in the OHE group, the phosphate was increased while magnesium and potassium were reduced.CONCLUSION: Hypothyroidism caused impaired renal function, glucose intolerance, hyperlipidemia, and reduction in serum phosphate. Hyperthyroidism caused a reduction in serum lipids, magnesium, and potassium. Thyroxine therapy normalized the deranged lipids and minerals, but not glucose. Results indicate that thyroid function tests should be considered when diagnosing those metabolic disorders.